The theory of potential and spherical harmonics - Sternberg, Wolfgang J., 1887-; Smith, Turner L. (Turner Linn), 1898- (Mathematical expositions, 1944)
The book is designed chiefly for the use of students and teachers. The research worker will perhaps find some helpful suggestions, as well. The student reading this book is presumed to have a thorough knowledge of differential and integral calculus. In some sections also an acquaintance with the most elementary theorems of the theory of analytic functions and of the theory of linear differential equations is desirable. The text offers a short introduction to vector analysis and a presentation of the Fredholm theory of integral equations. The theory of spherical harmonics is also briefly explained. Consistent use of vector analysis is a characteristic feature of the book. The authors hope that the present text fills a gap, by leading the student reader from the elements of potential theory to the solutions of boundary value problems in a simple and easily understandable way.